(m/9)+7=3

Simple and best practice solution for (m/9)+7=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m/9)+7=3 equation:



(m/9)+7=3
We move all terms to the left:
(m/9)+7-(3)=0
We add all the numbers together, and all the variables
(+m/9)+7-3=0
We add all the numbers together, and all the variables
(+m/9)+4=0
We get rid of parentheses
m/9+4=0
We multiply all the terms by the denominator
m+4*9=0
We add all the numbers together, and all the variables
m+36=0
We move all terms containing m to the left, all other terms to the right
m=-36

See similar equations:

| (N+10)3=8n | | n^2+4n-23=-8 | | 2x+3=102-7x | | x+53+70+64=180 | | 10n(3)=8n | | 2(4x+2)=-5(3x-1) | | X-7=4y/y=63/9 | | 33+15w=3w=3w-w+4w | | (2/3)(3x-6)=4(x+6) | | 4+2x=7x+59 | | 14=-7y+4(y+5) | | 3(10n)=8n | | 2(3x+2)=-5(3x-5)-4 | | 1.5(2x-4)=1.5x=3 | | 5/3x+3/4=4/9 | | -2x+5=6x-43 | | 5+3x=215 | | 2^2+4n-23=-8 | | 4x+6=-7x-5 | | 5x-2+3x-0.5+3x-0.5+5x-2=2x+3+2x+3+10x-5 | | g.|.4=2 | | 2x-14+x+17=90 | | -6x-4(-7x+9)=96 | | 90=9x+16 | | Y+78=7y | | -15r+5=30 | | 5x-3=215 | | -5h-5h+12h=-20 | | 3x+5=215 | | 2x/(685-85)=25 | | 3(6-z)-2=-z | | P+22=2p |

Equations solver categories